PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM UPAYA PENINGKATAN MOTIVASI KERJA PEGAWAI (Studi di Kantor Satuan Polisi Pamong Praja Kabupaten Lampung Timur) - Wahyu Widodo Wahyu Widodo (Derivatif : Jurnal Manajemen, 2015)
The research problems are how the role of human resource management in order to increase employee motivation to work? This study aims to determine the role of human resource management in order to increase employee motivation. The data collection technique used is using the interview / interview as the main engineering, documentation and observation as a technique of supporting the 10 informants. Based on the research results can be concluded as follows: The role of human resource management in the Office Sat.Pol.PP East Lampung district can be good, as shown by the education level of high school informant s / d Bachelor, and the employees are educated high school, many of which continue their education in college, Employees have a high motivation to follow the training and skills courses.